Pengaruh Penggunaan Meja Kursi Ergonomi Terhadap Kemampuan Koordinasi Motorik Anak Kelas 3 SD Alam Aqila Wonosari Klaten - Haris Sutopo; Iffah Nurhayati (Jurnal Keterapian Fisik, 2019)
Background: The effect of the use of ergonomic chair table, Motoric coordination, 3rd grade Elementary School.The purpose of the study was to determine the effect of the use of ergonomic chair tables on motoric coordination ability of grade 3 students at SD Alam Aqila Wonosari Klaten. Method: Data analysis was carried out through quantitative analysis with paired sample t-test and data compatibility test in both groups before treatment using parametric test (independent sample t-test), from the results of examination using VMI Beery, mean before use ergonomic chair table at 19.13 and after the use of ergonomic chair desk for 23.31. Result: The effect of using ergonomic chair table can be seen by comparing the data before and after using the ergonomics chair table using paired sample t-test. the value obtained with a 95% confidence level is -6,330 to -2,045. Conclusion: Use of Ergonomic Chair Tables can improve motoric coordination ability of grade 3 SD Alam Aqila Wonosari Klaten.